2013
DOI: 10.7314/apjcp.2013.14.10.5693
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Attitudes and Behavior of Relatives of Breast Cancer Patients Concerning Cancer Prevention and Screening

Abstract: Background: Changes in the attitudes and behavior of relatives of breast cancer patients concerning cancer prevention and screening after diagnosis in a loved one were evaluated. Materials and Methods: Forty-three questions were used to collect data from the relatives of the breast cancer patients who had been living with their relatives for at least one year. Results: The study group was composed of 171 female relatives (median age: 43, range: 17-82 yr). After the patients were diagnosed with breast cancer, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Our study found that women who had participated in health education programs about breast cancer screening and risk-stratified screening, having second degree relatives with breast cancer were more likely to have a positive attitude towards personalized risk-stratified screening. This finding could be explained that by previous study, the changes in attitudes and behaviour for breast cancer prevention and screening were found in the relatives of breast cancer diagnosed patients [ 24 ]. Therefore, personal experiences with breast cancer or family history of breast cancer might contribute to the attitude towards personalized risk-stratified screening [ 25 ].…”
Section: Discussionsupporting
confidence: 66%
“…Our study found that women who had participated in health education programs about breast cancer screening and risk-stratified screening, having second degree relatives with breast cancer were more likely to have a positive attitude towards personalized risk-stratified screening. This finding could be explained that by previous study, the changes in attitudes and behaviour for breast cancer prevention and screening were found in the relatives of breast cancer diagnosed patients [ 24 ]. Therefore, personal experiences with breast cancer or family history of breast cancer might contribute to the attitude towards personalized risk-stratified screening [ 25 ].…”
Section: Discussionsupporting
confidence: 66%
“…Additional risk factors related to development of breast cancer include nulliparity or pregnancy after the age of 30, ovarian activity, use of oral contraceptives, receiving hormone replacement therapy after menopause, lactation, alcohol consumption, obesity and high-fat diets and physical activity (Koc and Saglam, 2009;Alpteker and Avci, 2010;Amusu et al, 2011;Kanbur and Capik, 2011;Koca et al, 2013). In the present study, a very small percentage of the women cited genetic or familial predisposition as one of the risk factors for breast cancer and most of them (56.2%) were not aware of other risk factors and signs of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most common type of cancer among women with the highest fatality rates (Oluwatosin and Oladepo, 2006;Smith et al, 2006;Ozdemir et al, 2007;Montazeri et al, 2008;Habib et al, 2010;Amosu et al 2011;Sambanje and Mafuvadze, 2012;Shieh et al, 2012;Koca et al, 2013;Kratzke et al, 2013;Oztunc et al, 2013). Globally, cervical cancer is the second most prevalent cancer and third most common type of cancer after breast and lung cancers among women (Acikgoz et al, 2011;Adekanle et al, 2011;Sogukpinar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additional risk factors related to development of breast cancer include nulliparity or pregnancy after the age of 30, ovarian activity, use of oral contraceptives, receiving hormone replacement therapy after menopause, lactation, alcohol consumption, obesity and high-fat diets and physical activity (Amusu et al, 2011;Kanbur and Capik, 2011;Koca et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most common type of cancer among women with the highest fatality rates (Koca et al, 2013;Kratzke et al, 2013;Oztunc et al, 2013). Considering that breast cancer is the most common type of cancer among women with an increasing incidence, there is a need to develop community-based, wellorganized screening programs for breast cancer instead of coincidental screening of women (Acikgoz et al, 2011) because early diagnosis is the most effective way to reduce morbidity and mortality of breast cancer (Kanaga et al, 2011).…”
Section: Introductionmentioning
confidence: 99%